The Fat-Induced Satiety Factor Oleoylethanolamide Suppresses Feeding through Central Release of Oxytocin - Gaetani, Silvana (Society for Neuroscience, 2010)
Oleoylethanolamide (OEA) is a biologically active lipid amide that is released by small-intestinal enterocytes during the absorption of dietary fat and inhibits feeding by engaging the nuclear receptor, peroxisome proliferator-activated receptor-α (PPAR-α). Previous studies have shown that the anorexic effects of systemically administered OEA require the activation of sensory afferents of the vagus nerve. The central circuits involved in mediating OEA-induced hypophagia remain unknown. In the present study, we report the results of in situ hybridization and immunohistochemistry experiments in rats and mice, which show that systemic injections of OEA (5–10 mg kg(−1), intraperitoneal) enhance expression of the neuropeptide oxytocin in magnocellular neurons of the paraventricular nucleus (PVN) and supraoptic nucleus (SON) of the hypothalamus. No such effect is observed with other hypothalamic neuropeptides, including vasopressin, thyrotropin-releasing hormone and pro-opiomelanocortin. The increase in oxytocin expression elicited by OEA was absent in mutant PPAR-α-null mice. Pharmacological blockade of oxytocin receptors in the brain by intracerebroventricular infusion of the selective oxytocin antagonist, L-368,899, prevented the anorexic effects of OEA. The results suggest that OEA suppresses feeding by activating central oxytocin transmission.